Metabolic Syndrome and Rheumatic Diseases in Chad: Prevalence, Associated Factors and Clinical Impact - Harine Abdel Aziz Garba; Ramadhane Bouchrane; Adama Bah; Djikoldinguem Marschall Mouandilmadji; Harine Abdel Aziz Hamid; Moustapha Niasse; Saidou Diallo (European Scientific Journal, ESJ, 2025)
Objective: To assess the prevalence of metabolic syndrome (MS) and its clinical impact among patients with rheumatic diseases in Chad.Methods: A retrospective, cross-sectional, analytical study was conducted at the (HRT) Rheumatology Department from January 2018 to May 2024. Among 5000 patients, 330 fulfilled IDF and 214 WHO criteria for MS. Clinical, laboratory, and therapeutic data, as well as functional scores (SF-36, DAS28, BASFI, WOMAC), were systematically analyzed.Results: MS prevalence was 6.6% (IDF) and 4.3% (WHO). The cohort was predominantly female (88.7%), with a mean age of 49.8 ± 12.4 years. The most frequent components were abdominal obesity (93.0%), hypertension (89.7%), and hyperglycemia (64.8%). Associated diseases included connective tissue disorders (40.9%), degenerative conditions (34.3%), and autoinflammatory diseases (24.8%). After a mean two-year follow-up, functional and quality-of-life scores improved, although 13 patients developed cardio-renal complications. Conclusions: MS is common among rheumatology patients in Chad and worsens disease prognosis. Systematic screening and multidisciplinary management are essential to improve outcomes and quality of life.